2016
DOI: 10.1097/prs.0000000000002741
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Architecture Linked to Airway Obstruction and Intracranial Hypertension in Children with Syndromic Craniosynostosis

Abstract: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Although moderate to severe OSA has been shown to confer increased risk of ICH development in craniosynostosis, it has not resulted in cortical thickness changes in this study. The mechanism by which OSA is thought to contribute to ICH is through hypercapnia leading to altered cerebral hemodynamics .…”
Section: Discussionmentioning
confidence: 62%
“…Although moderate to severe OSA has been shown to confer increased risk of ICH development in craniosynostosis, it has not resulted in cortical thickness changes in this study. The mechanism by which OSA is thought to contribute to ICH is through hypercapnia leading to altered cerebral hemodynamics .…”
Section: Discussionmentioning
confidence: 62%
“…OSA may result in hypercapnia and subsequent vasodilatation of the cerebral vasculature which contributes to ICHT [32]. As a result of relaxation of the pharyngeal musculature, OSA occurs mainly in rapid eye movement sleep, when the intracranial pressure already rises due to increased blood flow [33]. OSA and intracranial pressure are interrelated and treatment of ICHT should go hand in hand.…”
Section: Article Highlightsmentioning
confidence: 99%
“…This is a multi-parametric test over night that captures electro-encephalography, heart rate, oxygen saturation, respiration movements, and intravenous CO 2 examination. PSG studies have shown a higher respiratory effort-related arousal index, lower sleep efficiency, and less rapid eye movement sleep in patients with syndromic craniosynostosis with moderate or severe OSA [33]. For follow-up, ambulant polygraphy may be considered [34].…”
Section: Article Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that children with sCS with no OSA or ICH have normal sleep pattern, which was determined by the presence of normal total sleep time (TST), normal number of arousals, and normal sleep architecture using electroencephalography (EEG) derived hypnograms (8). In contrast, sCS children with moderate-to-severe OSA had higher arousal index, higher respiratory effort-related arousal (RERA) index, lower sleep efficiency, less rapid-eye movement (REM) sleep, and more non-REM stage 1 (N1) sleep.…”
Section: Introductionmentioning
confidence: 99%